(untitled) (Scientific journal of the Fergana State University, 2026)
The article presents a comparative institutional analysis of active tourism organization models. It identifies the features of regulatory frameworks, certification, digital infrastructure, community involvement, and financial mechanisms. Based on the analysis, an adaptive strategy for Uzbekistan is proposed, integrating the strengths of international experience through four directions for sector transformation.